2016
DOI: 10.1080/21597081.2015.1128512
|View full text |Cite
|
Sign up to set email alerts
|

CTXφ: Exploring new alternatives in host factor-mediated filamentous phage replications

Abstract: For a long time Ff phages from Escherichia coli provided the majority of the knowledge about the rolling circle replication mechanism of filamentous phages. Host factors involved in coliphages replication have been fully identified. Based on these studies, the function of Rep protein as the accessory helicase directly implicated in filamentous phage replication was considered a paradigm. We recently reported that the replication of some filamentous phages from Vibrio cholerae, including the cholera toxin phage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The free 3′ end can now serve as a primer for the host DNA polymerase holoenzyme to synthesize a new + strand, displacing the original + strand as it progresses. In Ff, these pII‐mediated steps are also dependent on the host replicative Rep helicase and integration host factor, whereas some Vibrio and Pseudomonas Pf phages use the hosts alternate DNA repair helicase UvrD and the histone‐like HU proteins . Once the replication completes a full circle, pII cleaves and cyclizes the free ends resulting in a ssDNA IF and dsDNA RF .…”
Section: Filamentous Phage Life Cycle: Genome Replicationmentioning
confidence: 99%
“…The free 3′ end can now serve as a primer for the host DNA polymerase holoenzyme to synthesize a new + strand, displacing the original + strand as it progresses. In Ff, these pII‐mediated steps are also dependent on the host replicative Rep helicase and integration host factor, whereas some Vibrio and Pseudomonas Pf phages use the hosts alternate DNA repair helicase UvrD and the histone‐like HU proteins . Once the replication completes a full circle, pII cleaves and cyclizes the free ends resulting in a ssDNA IF and dsDNA RF .…”
Section: Filamentous Phage Life Cycle: Genome Replicationmentioning
confidence: 99%
“…In particular, cycles of excision and reintegration of CTXΦ promote the continuous apparition of clones producing new potentially more active forms of cholera toxin, which is a major clinical concern. The presence of an integrated copy of CTXΦ limits the possibilities for integration of new phage variants because it limits rolling-circle amplification of CTXΦ phages from the same incompatibility group (3639). Thus, excision of previously integrated CTX copies is crucial for the spreading of new toxin variants.…”
Section: Discussionmentioning
confidence: 99%
“…The HJs are converted into product by replication. CTXΦ integration is facilitated by rolling-circle replication, which amplifies the number of copies of its genome, and by a ubiquitous base excision repair enzyme, Endo III, which stabilizes HJs (3638). In contrast, TLCΦ integration depends on the addition of a full cross-over between its attachment site and dif1 by a yet poorly understood FtsK-independent Xer recombination reaction (15).…”
mentioning
confidence: 99%
“…Genome. Cross-talk between GIs and prophages in V. cholerae is a well-known phenomenon (29,30). However, the influence of acquired functions in the functionality of genes present in the core genome is not known.…”
Section: Cross-talk Between Horizontally Acquired Genetic Elements and Corementioning
confidence: 99%
“…Core Genome-Encoded RecA Helps CTXΦ to Overcome Host Immunity and Reinfect V. cholerae. Other than phage-encoded RstA, chromosomally encoded UvrD helicase and LexA also play an important role in CTXΦ replication (30). It was reported that RstR, the CTXΦ encoded transcriptional factor, binds to the rstA promoter (P rstA ) and represses its expression from the prophage genome (31).…”
Section: Cross-talk Between Horizontally Acquired Genetic Elements and Corementioning
confidence: 99%